A randomized trial comparing terlipressin and noradrenaline in patients with cirrhosis and septic shock. (20th October 2016) - Choudhury, Ashok; Kedarisetty, Chandan K.; Vashishtha, Chitranshu; Saini, Deepak; Kumar, Sachin; Maiwall, Rakhi; Sharma, Manoj K.; Bhadoria, Ajeet S.; Kumar, Guresh; Joshi, Yogendra K.; Sarin, Shiv K.
Abstract: Background & Aims: The choice of vasopressor for treating cirrhosis with septic shock is unclear. While noradrenaline in general is the preferred vasopressor, terlipressin improves microcirculation in addition to vasopressor action in non‐cirrhotics. We compared the efficacy and safety of noradrenaline and terlipressin in cirrhotics with septic shock. Patients and Methods: Cirrhotics with septic shock underwent open label randomization to receive either terlipressin (n=42) or noradrenaline (n=42) infusion at a titrated dose. The primary outcome was mean arterial pressure (MAP) >65 mm Hg at 48 h. Results: Baseline characteristics were comparable between the terlipressin and noradrenaline groups.SBP and pneumonia were major sources of sepsis. A higher proportion of patients on terlipressin were able to achieve MAP >65 mm of Hg (92.9% vs 69.1% P =.005) at 48 h. Subsequent discontinuation of vasopressor after hemodynamic stability was better with terlipressin (33.3% vs 11.9%, P <.05). Terlipressin compared to noradrenaline prevented variceal bleed (0% vs 9.5%, P =.01) and improved survival at 48 h (95.2% vs 71.4%, P =.003). Percentage lactate clearance (LC) is an independent predictor of survival [ P =.0001, HR=3.9 (95% CI: 1.85‐8.22)] after achieving the target MAP.Therapy related adverse effect were comparable in both the arms (40.5% vs 21.4%, P =.06), mostly minor (GradeII‐88%) and reversible. Conclusions: Terlipressin is as effective as noradrenaline as a vasopressor in cirrhotics with septic shock and can serve as a useful drug. Terlipressin additionally provides early survival benefit and reduces the risk of variceal bleed. Lactate clearance is a better predictor of outcome even after achieving target MAP, suggesting the role of microcirculation in septic shock.